ARABIC LINGUISTICS IN HISTORICAL AND ISLAMIC CULTURE PERSPECTIVES - Bachmid, Gayda (Center for Research and Development of Religious Literature and Heritage, 2016)
This writing confirms that the Arabic linguistic phenomena is cherished by its users even though the historical background reveals the users had limited competence. The research aim is to describe the determining reasons why the Arabic language is accepted and cherished by the Muslim community in Manado. The primary data source are the selected respondents in line with the religious social group representative category. The secondary data originates from the references. The research findings indicate that there are two main factors that explain why the Arabic language is revered by the user community, the elements are culture and history. Cultural study includes values, thinking patterns, convictions, admiration, sacredness, and the beauty of literary art, the richness of vocabulary that connects virtues and language. The historical context relates that Arabic linguistics is the language of prophecy, the language that shifted the ancient civilization to the modern era, and the translating language of science and technology as a powerful spirit that transforms and moves the Western world toward revival.